Clinical study on the influence of tea drinking habits on bone mineral density and osteoporosis in postmenopausal women in Fuzhou city, China - Li, Jian-Yang; Ge, Ji-Rong; Chen, Juan; Ye, Yun-Jin; Xie, Li-Hua; Li, Li; Chai, Hao (Progress in Nutrition, 2021)
Objective: To analyze the influence of tea drinking habits on bone mineral density (BMD) and osteoporosis (OP) in Chinese postmenopausal women in Fuzhou city after adjusting for the effects of confounding factors such as age, living habits, and diseases.Methods: 1134 cases of postmenopausal women living in Fuzhou city were randomly investigated, among which 947 cases met the requirements. There were 502 cases in the non-tea-drinking group, 326 cases in the occasional-tea-drinking group, and 119 cases in the daily-tea-drinking group. Researchers surveyed subjects' age, menopause age, living habits, disease, and other factors. Body mass index (BMI) was calculated based on height and weight. BMD in the lumbar spine and hip was measured by dual-energy X-ray (DXA) absorptiometry.Results: Among the 947 postmenopausal women, 53.1% were non-tea-drinkers, 34.42% were occasional tea-drinkers, and 12.57% were daily-tea drinkers. The lumbar spine BMD of the daily-tea-drinking group was (0.788±0.115) kg / cm2, which was higher than the non-tea-drinking group of (0.737±0.106) kg / cm2 (p